Simultaneous Determination of Na, K and Ca in Biodiesel by Flame Atomic Emission Spectrometry - Raposo,Juliana D. (2015)
This work aimed to develop a methodology for simultaneous determination of Na, K and Ca in biodiesel samples by flame atomic emission spectrometry, using a continuous electromagnetic radiation detector. Two procedures were employed for biodiesel sample preparation: direct dilution with kerosene and sample emulsification with HNO3, n-butanol and Triton X-100. The proposed methodology presented good linearity, relative standard deviations less than 5% and limits of quantification of 0.05 and 0.02 mg kg–1 for Na and K, respectively, using emulsification and solvent dilution. For Ca, the limit of quantification was 0.2 and 1.0 mg kg–1, applying direct dilution and emulsion, respectively. The emulsification procedure showed no matrix influence when recovery tests were performed (89-108%). Reference methodology (ABNT NBR 15553) was used to check the accuracy, presented consistent results at 95% confidence level, being suitable for biodiesel samples in a routine analysis.